SCHOOL PREPARATION AND EMPLOYMENT, ANCHORS FOR THE FUTURE - CLAUDIA ISAC; NICULETA PLEȘAN (Annals of the University of Petrosani: Economics)
Placing a person in the labour field represents an objective that favours their social integration, as a result of the professional training provided by the completion of a proposed education cycle. Is there a correlation between the professional training of young people and their insertion on the labour market, in accordance with the need for labour in a certain field? Is there an individual strategy regarding school preparation and employment projection, following the point of view of both students and their representatives? Here are some current research questions of interest both for the academic environment that comes with the educational offer, but also for employers formulating the demand from the labour market. In most countries, including Romania, the school holds the monopoly on staff training and qualification. The education system is not criticized for this monopolization, but for the fact that it fails to fully respond to the current and future needs of the labour market. Therefore, in recent years, the need to establish an appropriate correspondence between professional training and the labour market is increasingly being insisted upon.